Understanding and Managing Emerald Ash Borer Impacts on Ash Forests - Randall K. Kolka (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The emerald ash borer (EAB) is rapidly spreading throughout Eastern North America and devastating ecosystems where ash is a component tree. This rapid and sustained loss of ash trees has already resulted in ecological impacts on both terrestrial and aquatic ecosystems and is projected to be even more severe as EAB invades ash dominated wetlands of the western Great Lakes region. We propose a Special Issue that will address current research documenting ecological impacts of EAB in forest ecosystems, as well as management approaches to mitigate those impacts. Prospective authors are invited to contribute original researches to this Special Issue of Forests. Topics may include, but are not limited to: Managements of ash forests and potential replacements, nutrient and vegetation dynamics, greenhouse gas emissions and carbon sequestration and cycling, hydrologic impacts, and pre or post-infestation silvicultural approaches or management strategies.